Kelangkaan dalam Ekonomi Makro Islam: Analisis Dampak Keterbatasan Sumber Daya Terhadap Pertumbuhan Ekonomi - Amsari, Syahrul; Sahla, Hilmiatus; Abd Majid, M. Shabri; Afandi, Ahmad (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
This study aims to determine the impact of few resources on economic growth from an Islamic macroeconomic standpoint. A descriptive method was employed in this investigation. Documentation studies or written documents including data gathered from books, journals, the Central Bureau of Statistics' official website, and other publications were used as data gathering methods. The study's findings clarify that Islamic macroeconomics places a strong emphasis on socioeconomic justice, human brotherhood, and moral principles. To ensure everyone's well-being, it depends on markets, families, communities, value role play, and the government. Lack of material resources is not the root cause of economic issues. Since Allah SWT has made human needs available, the primary economic issue is not the availability of natural resources but rather human activity, which leads to scarcity. Naturally, limited resources, if controlled and used for a sustainable economy, will not slow down economic growth if everyone works hard, restricts demands, and can effectively manage the community's economy.